C75 PHEOCHROMOCYTOMA–INDUCED CARDIOGENIC SHOCK: A MULTICENTER ANALYSIS OF CLINICAL PROFILES, MANAGEMENT AND OUTCOMES. (18th May 2022) - De Angelis, E; Ravera, A; Ammirati, E; Tedeschi, A; Polito, M; Pieroni, M; Gentile, P; Merlo, M; Van De Heyning, C; Bekelaarh, T; Cipriani, A; Camilli, M; et al.
Abstract: Background: Pheochromocytoma is a rare neuroendocrine tumor that arises from the adrenal gland and overproduces catecholamines; it is an infrequent cause of cardiogenic shock (CS). Several case reports have investigated pheochromocytoma–induced CS, but larger studies have not yet been carried out. Objectives: Our work aims to describe a multicenter experience in the diagnosis and management of patients with pheochromocytoma–induced CS, and to raise awareness around this rare condition. Methods: We enrolled all patients with a diagnosis of pheochromocytoma–induced CS admitted to the intensive care units of 8 European referral Hospitals. Results: Among the 17 patients (47% males, mean age 49, 5 years), we found that pulmonary congestion was the mostly represented clinical feature (82%). The most represented echocardiographic left ventricle (LV) pattern was the reverse Takotsubo (TTS) pattern with apical hyperkinesis associated with basal– to mid–ventricular hypokinesis (47%). Elevated systemic vascular resistances (SVR) were observed. Endomyocardial biopsy of the LV was performed in one patient showing contraction band necrosis, oedema and inflammatory reaction. 76% of patients were treated with dobutamine, 70% needed noradrenaline, 29% adrenaline, 23.5% were treated with levosimendan and 17% with milrinone. Mechanical circulatory support devices (MCS) were necessary for 65% of patients. All patients benefited from pheochromocytoma's surgical excision, with 4 patients operated on while under ECLS. All patients recovered, excepted one (presenting a severe left ventricular dilatation at admission) who required cardiac transplantation. Conclusion: Pheochromocytoma is an infrequent cause of CS, with most often a TTS–like presentation. It should be suspected in case of a CS with high initial SVR and rapid deterioration. MCS must be considered in the most severe cases. The main challenge is to stabilize the patient, mostly with MCS, since it remains a reversible cause of CS with a low mortality rate. Adrenalectomy can safely be performed even when the patient is under MCS.